2010
DOI: 10.1164/rccm.201001-0077oc
|View full text |Cite
|
Sign up to set email alerts
|

Short, Highly Effective, and Inexpensive Standardized Treatment of Multidrug-resistant Tuberculosis

Abstract: Serial regimen formulation guided by overall treatment effectiveness resulted in treatment outcomes comparable to those obtained with first-line treatment. Confirmatory formal trials in populations with high levels of human immunodeficiency virus coinfection and in populations with a higher initial prevalence of resistance to second-line drugs are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
508
1
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(538 citation statements)
references
References 15 publications
11
508
1
18
Order By: Relevance
“…[42][43][44] The "Bangladesh'' shorter standardized regimen, achieved a relapse-free cure of 87.9% among 206 patients, this regimen achieved < 1% failure and 90% relapse-free cure. 45 Moreover, an update of this study has shown that 84.4% of the 515 patients had a bacteriologically favourable outcome. 40 The only difference between the Bangladesh regimen and the WHO shorter regimen is the substitution of gatifloxacin for moxifloxacin.…”
Section: Drug-resistant Tuberculosismentioning
confidence: 79%
“…[42][43][44] The "Bangladesh'' shorter standardized regimen, achieved a relapse-free cure of 87.9% among 206 patients, this regimen achieved < 1% failure and 90% relapse-free cure. 45 Moreover, an update of this study has shown that 84.4% of the 515 patients had a bacteriologically favourable outcome. 40 The only difference between the Bangladesh regimen and the WHO shorter regimen is the substitution of gatifloxacin for moxifloxacin.…”
Section: Drug-resistant Tuberculosismentioning
confidence: 79%
“…Nevertheless, drawbacks of significant toxicity and pill burden, poor adherence, and 6-8 months of painful injections with second-line injectable drugs remain. Also in 2016, WHO has recommended a standardised shorter MDR tuberculosis treatment regimen that has been used with second-line drug treatment-naïve patients with MDR tuberculosis in Bangladesh, 277 Niger, 278 and Cameroon. 279 The shorter MDR tuberculosis regimen (9-12 months) is successful in approximately 90% of cases, and includes three drugs (kanamycin, prothionamide, and high-dose isoniazid) for 4-6 months, with additional drugs (moxifloxacin, clofazimine, pyrazinamide, and ethambutol) …”
Section: Empirical Regimens In Usementioning
confidence: 99%
“…356 Clofazimine is also considered a key component of a short-course regimen (ie, 9-12 months) recently endorsed by WHO for treatment of MDR tuberculosis after several observational cohorts reported good treatment success. [277][278][279] Clofazimine is highly lipophilic, it has a very large volume of distribution, and has a terminal half-life of 70 days. The drug becomes highly concentrated in fat, organs, and skin with long-term use.…”
Section: Clofaziminementioning
confidence: 99%
“…The unfortunate development of multidrug-and extensively drug-resistant tuberculosis has kindled a worldwide push for the development of new therapy options for this disease, including a renewed interest in clofazimine (5). Although several groups have characterized clofazimine activity for in vitro and animal models of tuberculosis (6), a seminal publication by van Deun and colleagues in 2010 reported for the first time that a 9-month drug regimen including gatifloxacin, ethambutol, pyrazinamide, and clofazimine throughout plus a 4-month initial supplement of kanamycin, prothionamide, and a high dose of isoniazid achieved a relapse-free cure of 87.9% (95% confidence interval [CI], 82.7-91.6) among 206 patients in Bangladesh (7). Such a rate is higher than the 62% (95% CI, 57-67%) rate of successful outcomes reported in a recent systematic review of multidrug-resistant tuberculosis treatment (8), and it is also better than the 61% (95% CI, 53-69%) efficacy of the World Health Organization (WHO)-recommended two year-long retreatment regimen (9,10).…”
mentioning
confidence: 99%